Effects of Different Concentrations of Chitosan Oligosaccharides on Improving the Fruit Quality and Anthocyanin Content of Blueberry: A Mechanistic Study - HUANG Haiyan, XUE Yong, MAO Xiangzhao, JIANG Hong, HU Yang (Shipin Kexue, 2025)
This study investigated the effect of chitosan oligosaccharide treatment on the quality of blueberry fruit, with a particular focus on the types and contents of anthocyanins. After applying varying concentrations (0 (control), 25, 50, 100 mg/L) of chitosan oligosaccharide via foliar spraying or root drenching, single fruit mass, soluble solids content, hardness, and levels of VC, VE, total phenolics, flavonoids and anthocyanins were measured. The results showed that chitosan oligosaccharide treatment improved blueberry quality in a concentration-dependent manner, the effect being most pronounced at 50 mg/L concentration. Compared with the control group, 50 mg/L chitosan oligosaccharide increased the single fruit mass by 9.0%, horizontal diameter by 2.7%, vertical diameter by 4.9%, soluble solids content by 18.4%, and hardness by 15.6%. Additionally, this treatment enhanced the contents of total phenolics, flavonoids, VC, and VE by 21.7%, 28.6%, 79.6%, and 19.8%, respectively, while reducing the diversity of anthocyanins but significantly increasing the content of major anthocyanins. Total anthocyanin content increased by 7.0%, and the content of the major anthocyanin delphinidin by 1.3% when compared with the control. Furthermore, we found that chitosan oligosaccharide treatment could regulate the metabolic pathways of anthocyanin glycosides, and the enrichment of the 3MaT1, 3RT and 3GGT genes led to changes in the types and contents of anthocyanins. In summary, the application of chitosan oligosaccharide during the growth period of blueberry plants can effectively improve fruit quality, which is meaningful for guiding the improvement of blueberry cultivation technology.